Impact of emotional divorce on the mental health of married women in Saudi Arabia. - Hend Faye Al-Shahrani; Mohammad Ahmed Hammad (PLoS ONE, 2023)
Emotional divorce occurs when physical, psychological, mental, and spiritual separation occurs between spouses despite the fact that they live in the same house and exercise their marital duties. Emotional divorce has adverse effects on the mental health of those involved, as evidenced by the higher incidence of depression, anxiety, and loneliness among such couples. Saudi women are particularly vulnerable to emotional divorce owing to social, legal, economic, and cultural factors. Therefore, it is important to examine the relationship between emotional divorce and mental health issues (depression, anxiety, and loneliness) in married women in Saudi Arabia. Using scales that assess emotional divorce, depression, anxiety, and loneliness, data were collected from 241 married Saudi women (Mage = 34.41 years; SDage = 5.23 years). Findings revealed a statistically significant correlation between emotional divorce, depression, anxiety, and loneliness. One-way ANOVA confirmed that those with high levels of emotional divorce concurrently scores higher on the depression, anxiety, and loneliness tools, followed by those with moderate and low emotional divorce scores, respectively. Linear regression analysis indicated that depression, anxiety, and loneliness were strong predictors of emotional divorce, explaining 61% of the variance in the emotional divorce scores in this sample. These findings highlight the need to focus on the mental health outcomes of individuals experiencing emotional divorce, especially in societies where legal divorce may not be acceptable or encouraged. The need for regular evaluation and timely interventions for individuals struggling with mental health problems, and for restoring a healthy marital relationship is also highlighted.